2003
DOI: 10.1124/dmd.31.10.1235
|View full text |Cite
|
Sign up to set email alerts
|

EXPRESSION PROFILES OF DRUG-METABOLIZING ENZYME CYP3A AND DRUG EFFLUX TRANSPORTER MULTIDRUG RESISTANCE 1 SUBFAMILY mRNAS IN RAT SMALL INTESTINE

Abstract: This article is available online at http://dmd.aspetjournals.org ABSTRACT:The purpose of this study is to examine the expression profiles of CYP3A1, CYP3A2, CYP3A9, and CYP3A18 mRNAs as well as multidrug resistance (mdr)1a and mdr1b mRNAs in the liver and small intestine of normal male Wistar rats using a reverse transcriptionpolymerase chain reaction (PCR). In the rat liver, the PCR products for CYP3A1, CYP3A2, and CYP3A18 were readily detectable, whereas CYP3A9 was slightly and mdr1a and mdr1b barely detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 29 publications
5
42
1
1
Order By: Relevance
“…This finding is consistent with data published by Matsubara et al (2004), Takara et al (2003), and Takemoto et al (2003) showing decreasing expression of CYP3A mRNA and decreasing activity along the whole intestine. Even for the human equivalent CYP3A4 declining mRNA expression and activity profile along the human intestine could be demonstrated (Thummel et al, 1997).…”
Section: Mitschke Et Alsupporting
confidence: 83%
“…This finding is consistent with data published by Matsubara et al (2004), Takara et al (2003), and Takemoto et al (2003) showing decreasing expression of CYP3A mRNA and decreasing activity along the whole intestine. Even for the human equivalent CYP3A4 declining mRNA expression and activity profile along the human intestine could be demonstrated (Thummel et al, 1997).…”
Section: Mitschke Et Alsupporting
confidence: 83%
“…6, Table 3). Recent studies suggest that CYP3A9 as well as CYP3A18 may be the most abundantly expressed cytochromes P450 in rat intestine, whereas CYP3A1 and CYP3A2 may not be expressed at all (Takara et al, 2003). Debri et al (1995) reported that DEX induced a protein that cross-reacted with a CYP3A2 antibody, which recognized a C-terminal epitope in CYP3A2.…”
Section: Discussionmentioning
confidence: 99%
“…CYP3A9 and CYP3A18 levels were found to be higher than the levels of CYP3A1 or 3A2, and they decreased from the upper to the lower intestinal lumen, while Pgp expression increased gradually from the upper to the lower lumen. 26) Therefore, as possible reasons for the lack of KCZ effects on the portal levels of NFV or EM, there may not be sufficient amounts of CYP enzymes to catalyze these substrates in the rat small intestine, or the extraction rates of NFV and EM in the rat small intestine may be relatively small. Although KCZ has half the inhibitory potency of CsA for Pgp in the rat liver, KCZ did not show an inhibitory effect on Pgp in the rat small intestine, suggesting that the aspects of interaction between KCZ and Pgp differ in the liver and small intestine.…”
Section: Discussionmentioning
confidence: 99%